The role of [99mTc]Tc-HFAPi SPECT/CT in patients with malignancies of digestive system: first clinical experience. - Jia, Xi; Li, Xinru; Jia, Bing; Yang, Ye; Wang, Yuanbo; Liu, Yan; Ji, Ting; Xie, Xin; Yao, Yu; Qiu, Guanglin; Deng, Huixing; Zhu, Zhaohui; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2023)
Background: Recently, PET/CT imaging with radiolabelled FAP inhibitors (FAPIs) has been widely evaluated in diverse diseases. However, rare report has been published using SPECT/CT, a more available imaging method, with [99mTc]Tc-labelled FAPI. In this study, we evaluated the potential effect of [99mTc]Tc-HFAPi in clinical analysis for digestive system tumours. Methods: This is a single-centre prospective diagnostic efficiency study (Ethic approved No.: XJTU1AF2021LSK-021 of the First Affiliated Hospital of Xi'an Jiaotong University and ChiCTR2100048093 of the Chinese Clinical Trial Register). Forty patients with suspected or confirmed digestive system tumours underwent [99mTc]Tc-HFAPi SPECT/CT between January and June 2021. For dynamic biodistribution and dosimetry estimation, whole-body planar scintigraphy was performed at 10, 30, 90, 150, and 240 min post-injection in four representative patients. Optimal acquisition time was considered in all the patients at 60–90 min post-injection, then quantified or semi-quantified using SUVmax and T/B ratio was done. The diagnostic performance of [99mTc]Tc-HFAPi was calculated and compared with those of contrast-enhanced CT (ceCT) using McNemar test, and the changes of tumour stage and oncologic management were recorded. Results: Physiological distribution of [99mTc]Tc-HFAPi was observed in the liver, pancreas, gallbladder, and to a lesser extent in the kidneys, spleen and thyroid. Totally, 40 patients with 115 lesions were analysed. The diagnostic sensitivity of [99mTc]Tc-HFAPi for non-operative primary lesions was similar to that of ceCT (94.29% [33/35] vs 100% [35/35], respectively; P = 0.5); in local relapse detection, [99mTc]Tc-HFAPi was successfully detected in 100% (n = 3) of patients. In the diagnosis of suspected metastatic lesions, [99mTc]Tc-HFAPi exhibited higher sensitivity (89.66% [26/29] vs 68.97% [20/29], respectively, P = 0.03) and specificity (97.9% [47/48] vs 85.4% [41/48], respectively, P = 0.03) than ceCT, especially with 100% (24/24) specificity in the diagnosis of liver metastases, resulting in 20.0% (8/40) changes in TNM stage and 15.0% (6/40) changes in oncologic management. Conclusion: [99mTc]Tc-HFAPi demonstrates a greater diagnostic efficiency than ceCT in the detection of distant metastasis, especially in identifying liver metastases.